High sleep quality can increase the performance of CrossFit® athletes in highly technical- and cognitive-demanding categories - Kristina Klier; Selina Dörr; Annette Schmidt (BMC, 2021)
Abstract Background In current sports science, the important role of sleep quality for health and peak performance is well acknowledged. More precisely, it is evident that the negative combination of stressful factors, low resources, and bad sleep habits causes short-term performance losses as well as long-term health consequences. As the maximization of human performance consisting of multiple fixed workloads is the main motivation in CrossFit® (CF), the aim of the present study was to investigate the influence of high sleep quality on performance in CrossFit® athletes (CFA) and the different training categories that are addressed in CF. Methods In total, 149 CFA (81 females, 68 males; 32.01 ± 7.49 years old, 2.56 ± 1.77 active years in CF) filled in the online survey comprising the Pittsburgh Sleep Quality Index (PSQI) and CF performance-specific questions. Results It was found that CFA with high sleep quality reported higher values in all performance-related outcomes. Especially in Hero-/Girl-Workouts (χ2 = (1, n = 83) = 9.92, p = .002, φ = 0.37) and Gymnastics (χ2 = (1, n = 129) = 8.74, p = .003, φ = 0.28), performance differed significantly between good and poor sleeping CFA. Since those CF categories are highly technical- and cognitive-demanding high sleep quality seems to play a fundamental role in complex motor skill learning and performance development. Conclusions These results reveal for the first time the positive effects of high sleep quality for performance in CFA and could be used as basis for future studies. Future research should also develop and empirically test suitable interventions to foster high sleep quality in CFA. Trial Registration: The study was conducted according to the guidelines of the Declaration of Helsinki, and approved by the Ethics Committee of University of the Federal Armed Forces Munich, Germany (06/04/2018).